Assessing discard consumption dynamic in shallow coastal environment using underwater video - Lejeune, Benjamin; Marcout, Anna; Kopp, Dorothee; Morandeau, Fabien; Mehault, Sonia; Mouchet, Maud (Fisheries Research, 2023)
International audience Food webs are typically studied with respect to predator-prey interactions while often neglecting to address the role or importance of scavenging (i.e. carrion consumption) on their structure and functioning. In some environmental contexts, scavenging can play a key role in supporting populations and communities as exemplified by seabirds feeding on fisheries discards. Yet, a substantial part of fisheries discards sinks in the ocean where the range of consumers is most likely underestimated, owing to a lack of comprehensive understanding of the scavenging ability of marine fauna and local-scale empirical studies. Here, we deployed baited remote underwater video surveys (BRUVs) using discarded fish as baits to study the taxonomic richness of consumers, their interactions and consumption dynamic of discards in shallow coastal fishing grounds subject to discarding (Bay of Bourgneuf, North East Atlantic, France). We show that discards attract and are consumed by a wide taxonomic and trophic diversity of species. Interestingly, only one species observed is considered an obligate scavenger, while scavenging is little known or considered anecdotal in most other identified taxa. Analysis of consumption dynamic and interactions around discards revealed intra and interspecific competition among discard consumers as well as successions between consumers involved in predator-prey interactions. Data also suggests that decapods may facilitate discard consumption by non-piscivorous fish by generating scraps during consumption. We argue that underwater video surveys provide a valuable tool to better assess the occurrence and extent of facultative scavenging behaviors within marine communities and understand its role in food web dynamic.